Keanekaragaman Jenis Mamalia Besar di Kawasan UPT. Laboratorium Alam Hutan Gambut (LAHG) Sebangau Kalimantan Tengah: Diversity of Large Mammal Species in the UPT Peat Swamp Forest Nature Laboratory (LAHG) Sebangau, Central Kalimantan - Madiyawati, Milad; Rizal, Moh.; Nababan, Gabriella SN; Junaedi, Ajun; Mujaffar, Ahmad; Toni, Hendra (HUTAN TROPIKA, 2023)
Kalimantan has 222 species of mammals and 44 of them are endemic. This study aims to calculate the diversity and determine the number of large mammal species that exist in the UPT area. Natural Laboratory of Peat Forest (LAHG) Sebangau University of Palangka Raya, Central Kalimantan. The results of the research are There are 5 types of large mammals found through observation and interviews, namely Gibbon (Hylobates albibarbis), Classi (Presbytis baricunda), Orangutan (Pongo pygmaeus), Wild boar (Sus barbatus) and Sun Bear (Helarctos malayanus). Diversity Index of large mammal species in the UPT Area. Large mammal species diversity index in the UPT area. The Sebangau Peat Forest Nature Laboratory (LAHG) showed that it was classified as low, namely 0.97, the species richness index of large mammals in the UPT area. The Sebangau Peat Forest Nature Laboratory (LAHG) is classified as low, namely 0.96. The low number of individuals found in swamp and lowland habitats is related to the insufficient availability of feed in these habitats. This is caused by environmental conditions, namely peat swamps which are always wet and stagnant. And the index of evenness of large mammal species in the UPT area. The Sebangau Peat Forest Nature Laboratory (LAHG) is classified as high, namely 0.88. This has caused the discovery of mammals in the LAHG area to appear evenly distributed because there is no dominance between each species in the community.